2014
DOI: 10.1155/2014/980232
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Electrical Current and Zinc Sulphate Administered by Transdermal Iontophoresis Improves Skin Healing in Diabetic Rats Induced by Alloxan: Morphological and Ultrastructural Analysis

Abstract: Purpose. Evaluated the effects of continuous electrical current (CEC) or zinc administrated by transdermal iontophoresis (Zn+TDI). Methods. 120 male Wistar rats were submitted to an incision surgery at the anterior region of abdomen and distributed into 6 experimental groups with 40 animals: 3 diabetic groups and 3 normal groups, untreated and treated with CEC alone or with Zn + TDI. Each group was further divided into 4 subgroups with 10 rats each to be evaluated on the 4th, 7th, 14th, and 21st day after surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
1
10
0
2
Order By: Relevance
“…In this work, we combined the properties of these substances through the development of a new chitosan membrane modified with [Zn(phen)(van) 2 ] complex and evaluated the delivery capacity of compound in an aqueous medium and the wound healing activity in diabetic rats. Other authors corroborate the data obtained in this research, where dressings or compounds based on zinc and or chitosan increased wound healing in rat models (Kumar et al, 2012; Cassettari et al, 2013, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…In this work, we combined the properties of these substances through the development of a new chitosan membrane modified with [Zn(phen)(van) 2 ] complex and evaluated the delivery capacity of compound in an aqueous medium and the wound healing activity in diabetic rats. Other authors corroborate the data obtained in this research, where dressings or compounds based on zinc and or chitosan increased wound healing in rat models (Kumar et al, 2012; Cassettari et al, 2013, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…A previous study showed that topical zinc through the use of transdermal iontophoresis can increase the breaking strength in skin scars and accelerate wound healing in diabetic rats. 27 Furthermore, it has been reported that topical application of zinc oxide in wound of diabetic rat significantly inhibited bacterial growth in granulation tissue, which disclosed one of the potential underlying mechanisms through which zinc supplement promote wound healing of diabetes. In the current study, we found that spraying a topical 4% ZnSO 4 solution could promote vascular regeneration and tissue reconstruction in wound healing, thereby accelerating wound healing in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“… 23 - 25 Therefore, topical application of zinc in diabetic wounds has shown the promise in a diabetic rat model. 26 , 27 …”
Section: Introductionmentioning
confidence: 99%
“…The relationship between Zn deficiency and DM has been the subject of many studies, some using animal models [33][34][35] and some human subjects [36,37]. Diabetic subjects are commonly tested for blood glucose levels due to inadequate levels of insulin produced by the pancreas.…”
Section: Improvements In Control Diabetic Glycaemic Level After Zinc mentioning
confidence: 99%